FACTORS AFFECTING TRANSPORT DEVELOPMENT - Jumayev Xayrulla Xayitovich; Qurbonov Akrom Ernazarovich (The Conference Hub, 2025)
This work analyzes the role of the transport system in the development of society and the main factors influencing its development. Economic growth, population growth, urbanization processes, the development of innovations and technologies, as well as geographical factors are of great importance in the renewal and improvement of transport infrastructure. Also, the reforms implemented in the transport sector and international cooperation programs are highlighted on the example of Uzbekistan. The article has a practical orientation and puts forward proposals for the sustainable development of the transport system.
Keywords: transport, economic factors, social factors, innovation, logistics, infrastructure, globalization.